The efficacy of droperidol, metoclopramide, propofol and ondansetron for the prevention of nausea and vomiting following middle ear surgery - Karlıdağ, Turgut; Kaygusuz, İrfan; Keleş, Erol; Demirbağ, Erhan; Yalçın, Şinasi; Bestaş, Azize (İstanbul Üniversitesi, 2002)
Objectives: The efficacy and reliabilrty of prophylactic antiemetic therapy with low dose propofol, droperidol, metoclopramide and ondansetron were evaluated in a randomized, double- blind, and prospective design.Patients and Methods: A total of 101 ASA l-ll patients 34 females, 67 males; age range 16 to 53 years undergoing middle ear surgery for chronic otitis media or its sequelae were randomly assigned to receive prophylactic antiemetic therapy with propofol n=21,0.5 mg/kg , droperidol n=19,20 mg/kg , metoclopramide n=23, 0.2 mg/kg , ondansetron n=21,4 mg , and placebo n=20, 0.9% NaCI . Ali drugs were administered intravenously five minutes before extubation.Results:İn the early postoperative period 0 to 3 hours , the percentages of patients free from nausea and vomiting were 100% with droperidol, 71.4% with ondansetron and propofol, 52.1% with metoclopramide, and 35% with placebo.Ondansetron 90.4% was found the most effective to pre- vent and control nausea and vomiting during the postopera tive 3 to 24 hours, follovved by droperidol 84.2% , propofol 57.1% , metoclopramide 47.8% , and placebo 40% .Compared with Controls, the number of patients vvithout nau sea and vomiting was significantly greater in each treatment group but metoclopramide p

A m aç : Orta kulak cerrahisi sonrası oluflan bulantı-kusmanın profilaktik tedavisinde düflük doz propofol, metoklopramid, on- dansetron ve droperidolün etkinlik ve güvenilirliği rastgele se- çimli, çift-kör ve prospektif bir çalıflma düzeneğiyle arafltırıldı. Hastalar ve Yöntemler: Kronik otit veya sekeli nedeniyle orta kulak cerrahisi uygulanan, ASA I-II 101 hasta rastgele seçimle befl gruba ayrıldı. Ekstübasyondan befl dakika önce her bir gruba propofol n=21, 0.5 mg/kg , droperidol n=19, 20 mg/kg , metoklopramid n=23, 0.2 mg/kg , ondansetron n=21, 4 mg ve plasebo n=20, %0.9 NaCl intravenöz olarak uygulandı. Bulgular: Ameliyattan sonraki ilk üç saatlik dönemde dro- peridol alan hastaların hiçbirinde, ondansetron ve propofol gruplarının %71.4’ünde, metoklopramid grubunun %52.1’inde ve kontrol grubunun %35’inde bulantı-kusma görülmedi. Üç ile 24 saat arasındaki dönemde ise bulantı- kusmayı en iyi kontrol eden ajanın ondansetron %90.4 olduğu görüldü; bunu droperidol %84.2 , propofol %57.1 , metoklopramid %47.8 ve plasebo %40 izledi. Erken ve geç dönemde bulantı-kusma görülmeyen hasta sayısı, metoklopramid grubu dıflında, kontrol grubundan anlamlı derecede fazla bulundu p
Orta kulak cerrahisi sonrasında oluşan bulantı ve kusmada droperidol, metoklopramid, propofol ve ondansetronun etkinliği